Mecanismos de ação e controle da digestão de proteínas e peptídios em humanos - Frenhani, Patrícia Baston [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 1999)
This review aims to report the major control mechanisms of protein and peptides digestion of special interest in human patients. Regarding protein assimilation its digestive process begins at the stomach with some not so indispensable actions comparatively to those of duodenal/jejunal lumen. However even the intestine processes are partially under gastric secretion control. Proteolytic enzyme activities are related to protein structure and amino acid constituents, tertiary and quartenary structures need HCl - denaturation prior to enzymatic hydrolysis. Thereafter the exopeptidases are guided by either NH 2 (aminopeptidases) or COOH (carboxypeptidases) terminals of the molecule while endopeptidases are oriented by the specific amino acids constituents of the peptide. Both dietary and luminal secreted proteins and polypeptides undergo to either limited or complete proteolysis resulting basic or neutral free-amino acids (40%) or dioctapeptides. The brush border peptidases continue to degrade oligopeptide to di-tripeptides and neutral free-amino acids. Some peptides are uptaked by the enterocytes whose cytosolic peptidases complete the hydrolysis. Hence the digestive products flowing in the portal vein are mainly free-amino acids from either luminal or cytosolic hydrolysis and some di-tripeptides intactly absorbed. Both mechanical and chemical processes of digestion are under neural (vagal), neuroendocrinal(acetilcholine),endocrinal(gastrin, secretin and cholecystokinin) or paracrinal (histamine) controls. The gastric phase (hydrochloric acid and pepsinogen secretions) is activated by gastrin, histamine and acetilcholine which respond to both dietary-amino acids (tryptophan and phenylalanine) and mechanic distention of stomach. The pancreatic secretion is stimulated by either cephalic or gastric phases and has influence on the intestinal phase of digestion. The intestinal types of cells S and I release secretin and cholecystokinin respectively in response of acid quimo (cells S) or amino acids and peptides (cells I) in the lumen. Secretin stimulates the releasing of water, bicarbonate and enteropeptidases whereas cholecystokinin acts on pancreatic enzymes.
Human protein digestive activity and control
Keywords: Digestion; Peptides; Proteins; peptide; peptide hydrolase; protein; algorithm; chemistry; digestion; enzymology; human; intestine; intestine absorption; metabolism; physiology; protein intake; review; stomach; Algorithms; Dietary Proteins; Humans; Intestinal Absorption; Intestines; Peptide Hydrolases; Stomach